Contributo para a classificação da funcionalidade na população com mais de 65 anos, segundo a Classificação internacional de funcionalidade - Pereira, Carla (2018)
Purpose: Identification of categories of the International Classification of Functioning (ICF), disability and health, for the classification of functioning in the population over 65 years of age. Objective: To identify the more referred areas and ICF categories to classify the population over 65 years of age. Methodology: Literature review performed in CINAHL (Plus with Full Text, MEDLINE with Full Text). We searched scientific papers published in Full Text (February 2010) between 01.01.2000 and 31.01.2010, using the IP [C] O. Of 505 articles retrieved, 17 articles were selected because they were the ones who made reference to the most representative ICF categories for the population over 65 years. Results: We identified 252 categories that characterize the functionality of the population over 65 years of age. With the frequency description of ≥ 30%, 79 categories were observed, which are divided into three of the four ICF components. In the Body Functions component the identified categories were: Global mental functions (b110, b114, b130, b134); Specific mental functions (1-40, b144, b152, b167); Vision and related functions (b210); Hearing and vestibular functions (b230); Pain (b280); Voice and Speech Functions (b310); Cardiovascular functions (b410, b420); Haematological and immunologic functions (b430, b435); Respiratory system functions (b440); Digestive system related functions (b510, b525). In the Body Structures component the identified categories were: Nervous system structures (s110) Cardiovascular, immune and respiratory system structures (s410, s430); Movement related structures (s760). In the Activities and Participation component the identified categories were: Intentional sensory experiences (d110); Basic learning (d155); Knowledge application (d160, d166, d170, d175, d177); Tasks and general demands (d220, d230, d240); Communicate and receive messages (d310, d315); Communicate and produce messages (d330, d335, d345); Conversation and use of communication devices and techniques (d350, d360); Changing and maintaining body position (D410, d415, d420) Transporting, moving and handling objects (d430, d440, d445); Walking and travel (d450, d460, d465); Self care (d540, d550, d560, d570); Providing for the bare necessities of life (d620); Housekeeping (d640); Interpersonal relationships (d760); Community, social and civic life (d910). The most often mentioned categories in the environmental factors component were: Products and Technology (e110, e115, e120, e125, e150); Natural and man-made environmental changes (e260); Support and relationships (e310, e315, e320, e355, e360); Attitudes (e410, e415, e420, e450, e455, e465); Services, systems and policies (e570, e575, e580). Conclusions: The total of identified categories are distributed as follows: 83 categories of Body Functions component (32.93%); 12 articles, 30 categories of Body Structures component (11.90%); 7 articles, 82 categories of Activities and Participation component (32.53%); 16 articles, 57 categories of Environmental Factors component (22.61%) in 15 articles. The identification of these categories provides a working base to start the population over 65 year's characterization process in the national context.